On Strong Coupled Coincidence Points of g-Couplings and an Application. (12th July 2018) - Rashid, Tawseef; Khan, Qamrul Haq; Aydi, Hassen
Abstract : The purpose of this paper is to prove the existence and uniqueness of a strong coupled coincidence point ofF : X × X → X andg : X → X, involving Banach and Chatterjea typeg -couplings. We also give some examples and an application in support of the given concepts and our main results.